681 Ventricular fibrosis affects diastolic function and atrial remodelling long-term after aortic valve replacement for aortic valve stenosis. (8th December 2021) - Tadiello, Enrico; Trento, Laura; Setti, Martina; De Conti, Giorgia; Onorati, Francesco; Faggian, Giuseppe; Zamboni, Mauro; Rossi, Andrea; Benfari, Giovanni; Ribichini, Flavio
Abstract: Aims: Aortic stenosis (AS) is characterized both by progressive valve narrowing and left ventricular remodelling response. Myocardial fibrosis has significant functional consequences and is the key pathological process driving left ventricular decompensation. Furthermore, studies suggest that myocardial fibrosis is irreversible, despite surgical aortic valve replacement (SAVR). The study aims to define the association between myocardial fibrosis and long-term diastolic and atrial function after SAVR, which are both markers of poor clinical outcomes. Methods: We evaluated patients with isolated AS and no-coronary artery disease referred for SAVR in 2015. All of them received a biological valve and a left ventricular biopsy was performed at the time of surgery. Clinical and echocardiographic evaluation was performed before surgery and after about 6 years, including fully automated 2D speckle tracking analysis software (TomTec). Atrial function was evaluated with PALS, PACS, and LAVi/septal a' TDI. Results: Nineteen patients completed the follow-up and formed the study cohort, age 72 ± 6 years, 42% female, ejection fraction 63 ± 6.4%, mean fibrosis 26.4 ± 12.7%. Significant myocardial fibrosis (> 33%) was found in 13/19 patients (68%). Although similar at baseline, after 5.6±0.5 years, PACS was significantly higher in patients with low myocardial fibrosis (13.7±4.2 vs. 8.0±3.8, P =0.01), the same trends were observed for PALS (24.1±7.9 vs. 17.0±6.6, P =0.07) and LAVi/septal a'TDI (5.4±1.3 vs. 7.4±2.8, P =0.06). The diastolic profile at long term follow-up was also significantly worsened in patients with LV fibrosis: E/A 0.9±0.3 vs. 1.3±0.4 P = 0.03 and E/e' 10.6±3.3 vs. 16.6±4.5 P =0.01). Conclusions: Myocardial fibrosis at the time of SAVR strongly influences long-term diastolic Doppler profile and atrial function with potentially harmful consequences on clinical status and ventricular performance.